Granule
By mixing crystalline cellulose with mucopolysaccharides and performing kneeing and granulating during the granule preparation, the problems of fine powder generation and raw material loss in granule preparation are solved, and the good appearance and fluidity of the granule are achieved.
Patent Information
- Application Number
- JP2024171183
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-29
- Filing Date
- 2024-09-30
- Publication Date
- 2025-04-10
AI Technical Summary
When preparing drug particles, it is difficult to simultaneously inhibit the formation of fine powder, maintain the spherical appearance and reduce raw material losses.
By mixing crystalline cellulose with mucopolysaccharides and kneeing and granulating during the granulation process, particle size and shape are controlled to improve fluidity and reduce fine powder generation.
The good appearance and fluidity of the particles are achieved, the fine powder generation and raw material losses are reduced, and the quality and production efficiency of the particles are improved.
Smart Images

Figure 2025060575000001 
Figure 2025060575000002 
Figure 2025060575000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a granule, and more particularly to a granule containing crystalline cellulose and mucopolysaccharide. [Background technology]
[0002] Oral solid preparations containing various functional ingredients include tablets, capsules, granules, etc. Among these, granules are widely used because they can be taken without water, are easy to swallow, and are a dosage form that is easy for the elderly and children to take.
[0003] Methods for producing such granules typically include a wet granulation method in which functional ingredients and additives are mixed, granulated using a solvent such as water, and then dried, and a dry granulation method such as compaction granulation.
[0004] When producing granules, various binders and excipients are used depending on the purpose of production (for example, Patent Document 1). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2017-71561 A Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide a granule having good properties. [Means for solving the problem]
[0007] The size of granules affects the appearance and sensory quality of the formulation. Furthermore, the size of granules also affects the fluidity required in the manufacturing process, so the particle size is controlled in the granulation process to improve the fluidity. However, when preparing granular formulations, it is difficult to suppress fine powder and keep the loss of raw materials during manufacturing low while maintaining a beautiful spherical appearance. In other words, problems such as crushing and powdering of granules during the manufacturing process can occur.
[0008] As a result of intensive research conducted by the inventors to solve the above problems, they discovered that by preparing a granule containing crystalline cellulose and mucopolysaccharide, it is possible to produce granules with less fine powder during preparation, thereby reducing production losses, and thus completed the present invention.
[0009] That is, the present invention provides the following granules. [1] (A) crystalline cellulose; and (B) Granules containing mucopolysaccharides. [2] The granule according to [1], having an average particle size of 250 μm or more. [3] The granule according to [1] or [2], wherein the total content of the component (B) is 0.00001 to 40 parts by mass per part by mass of the component (A). [4] The granule according to any one of [1] to [3], having an aspect ratio of 1.0 to 3.5. [5] The granule according to any one of [1] to [4], wherein the particle size distribution ratio (M1 / M2) is 2.5 or more and 40 or less. [6] The granule according to any one of [1] to [5], having a surface roughness (Ra) of 1 or more and 40 or less. [7] The granule according to any one of [1] to [6], which is enclosed in a package that allows the contents to be visually confirmed. [8] The granule according to any one of [1] to [7], wherein component (B) is hyaluronic acid. [9] A step of mixing (A) crystalline cellulose and (B) mucopolysaccharide to prepare a mixture; and and kneading and granulating the mixture.
[10] A method for suppressing the generation of fine powder during granulation of a mixture containing (A) crystalline cellulose and (B) mucopolysaccharide. Effect of the Invention
[0010] According to the present invention, it is possible to provide good granules that maintain a regular spherical shape. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Normally, the granulation process is controlled by adjusting the ingredients and amounts of binders (e.g. HPMC, HPC) and excipients (starch, lactose). However, in the manufacturing process of granules, it can be difficult to prevent pulverization, and so far this has been dealt with by sieving the powder. However, this type of manufacturing process generates production losses, which also affect the quality of the product.
[0012] In the present invention, it has been clarified that the incorporation of crystalline cellulose and mucopolysaccharides can increase the water absorption of the raw material composition during the manufacturing process and further suppress pulverization. This makes it possible to produce granules with reduced pulverization and reduce production losses.
[0013] In the numerical ranges described in stages in this specification, the upper or lower limit of a certain numerical range can be arbitrarily combined with the upper or lower limit of another numerical range. In the numerical ranges described in this specification, the upper or lower limit of the numerical range may be replaced with a value shown in the examples. Unless otherwise specified, the components or materials exemplified in this specification may be used alone or in combination of two or more.
[0014] [Granules] ((A) Crystalline cellulose) The crystalline cellulose used in the present invention is not limited, but may be obtained by partially depolymerizing cellulose obtained from regenerated fibers or pulp with an acid or alkali, etc., and purifying it. The crystallinity, average polymerization degree, loss on drying, and bulk density of the crystalline cellulose are not particularly limited.
[0015] The degree of crystallinity of the crystalline cellulose is not limited, but is preferably 10% or more, more preferably 20% or more, and even more preferably 40% or more, as determined by X-ray diffraction.
[0016] The average degree of polymerization of the crystalline cellulose is not limited, but is preferably about 60 to 375, and more preferably about 100 to 350.
[0017] The loss on drying of the crystalline cellulose is not limited, but is preferably 1.0 to 8.0%, more preferably 2.0 to 7.0%, and even more preferably 2.0 to 6.0%.
[0018] The average particle size of the crystalline cellulose is not limited, but is preferably 10 to 170 μm, more preferably 20 to 90 μm, even more preferably 30 to 70 μm, even more preferably 40 to 60 μm, and most preferably 50 μm.
[0019] The angle of repose of crystalline cellulose is not limited, but is preferably from 10 to 60 degrees, more preferably from 20 to 55 degrees, even more preferably from 30 to 50 degrees, even more preferably from 40 to 50 degrees, and most preferably 45 degrees.
[0020] The water absorbency of crystalline cellulose is not limited, but is preferably 60 to 250%, more preferably 110 to 300%, even more preferably 120 to 260%, even more preferably 150 to 230%, and most preferably 200%.
[0021] The oil absorbency of the crystalline cellulose is not limited, but is preferably 60 to 250%, more preferably 90 to 210%, even more preferably 100 to 160%, even more preferably 110 to 150%, and most preferably 120%.
[0022] The bulk density of the crystalline cellulose is not limited, but is preferably 0.20 to 0.46 g / cm. 3 is preferably 0.20 to 0.40 g / cm 3 More preferably, 0.25 to 0.35 g / cm 3 The average degree of polymerization, loss on drying and bulk density are values measured by the method described in the identification test, loss on drying and bulk density, in the Japanese Pharmacopoeia, 18th Edition, Pharmaceutical Articles, Crystalline Cellulose.
[0023] In the granules of the present invention, the total content of the (A) component relative to the total amount is preferably 1% by mass or more, more preferably 3% by mass or more, more preferably 5% by mass or more, and even more preferably 7% by mass or more. The total content of the (A) component relative to the total amount of the granules is preferably 90% by mass or less, more preferably 80% by mass or less, even more preferably 70% by mass or less, and most preferably 60% by mass or less. It may also be 50% by mass or less, 40% by mass or less, 30% by mass or less, etc.
[0024] ((B) Mucopolysaccharides) The mucopolysaccharides used in the present invention are polysaccharides consisting of a repeating structure of hexosamine (glucosamine, galactosamine) and uronic acid, and are also called glycosaminoglycans. Examples of mucopolysaccharides include hyaluronic acid, chondroitin, jaluronic acid, heparan, keratan, and salts thereof. Examples of these salts include alkali metal salts (sodium salts such as sodium hyaluronate, etc.), sulfated glycosaminoglycans (chondroitin sulfate I, etc.), and the like. The sulfated glycosaminoglycans may be salts such as metal salts of sodium, potassium, calcium, magnesium, iron, manganese, etc., and ammonium salts. These mucopolysaccharides may be used alone or in combination of two or more.
[0025] Among mucopolysaccharides, acidic mucopolysaccharides having an acidic group such as carboxylic acid in the structure are preferred, including hyaluronic acid or its salts (such as sodium hyaluronate), chondroitin or chondroitin sulfate or its salts (such as metal salts of chondroitin sulfate). In particular, hyaluronic acid or its salts are more preferred. Although the mechanism of action is not entirely clear, mucopolysaccharides are negatively charged due to the presence of sulfate groups, uronic acid, etc., and can retain a large amount of water within the molecule, and therefore are considered to be able to achieve the effects of the invention.
[0026] The origin and molecular weight of hyaluronic acid or its salt are not limited, and it can be extracted from animal tissue or produced by fermentation method by culturing microorganisms. It can also be commercially available hyaluronic acid or its salt. The average molecular weight of hyaluronic acid or its salt may be about 2,000 to 1.7 million, about 10,000 to 1 million, or it may be hyaluronic acid with an average molecular weight of 500,000 or less. The average molecular weight of hyaluronic acid or its salt may be 2,000 to 200,000, 10,000 to 100,000, 200,000 to 2 million, 500,000 to 1.7 million, 1 million to 1.5 million, etc.
[0027] In the granules of the present invention, the total content of the (B) component relative to the total amount is preferably 0.001% by mass or more, more preferably 0.01% by mass or more, even more preferably 0.04% by mass or more, and even more preferably 0.1% by mass or more. The total content of the (B) component relative to the total amount of the granules is preferably 40% by mass or less, more preferably 30% by mass or less, even more preferably 20% by mass or less, and even more preferably 10% by mass or less.
[0028] The daily intake of the component (B) may vary depending on the condition of the individual taking it (body weight, age, sex, etc.), the formulation form of the composition, etc., but from the viewpoint of significantly exhibiting the effects of the present invention, it is, for example, preferably 1 mg or more, more preferably 5 mg or more, and even more preferably 10 mg or more. It may also be 2000 mg or less, preferably 1000 mg or less, more preferably 250 mg or less, and even more preferably 50 mg or less.
[0029] The amount of the (B) component per 1 part by mass of the (A) component is not limited, but is preferably 0.00001 to 40 parts by mass, more preferably 0.0001 to 10 parts by mass, even more preferably 0.0005 to 4 parts by mass, and even more preferably 0.001 to 1.5 parts by mass, and may also be 0.0002 to 10 parts by mass, 0.001 to 4 parts by mass, or 0.003 to 1.5 parts by mass.
[0030] (Liposomes) The granule of the present invention may further contain a liposome as an optional component. Here, the liposome is a closed endoplasmic reticulum of a single or multiple layer of phospholipids, and may contain a desired component in the internal aqueous layer or lipid layer. In this specification, the liposome containing the desired component is also referred to as "liposome". Such components that may be incorporated into the liposomes include, but are not limited to, vitamins (e.g., vitamin A [e.g., retinal, retinol, retinoic acid, carotene, dehydroretinal, lycopene, etc.], vitamin B [e.g., thiamine, thiamine disulfide, dicethiamine, octotiamine, shikotiamine, bis-ibuthiamine, bis-bentiamine, prosultiamine, benfotiamine, fursultiamine, riboflavin, flavin adenine dinucleotide, pyridoxine, pyridoxal, hydroxocobalamin, cyanocobalamin, methylcobalamin, deoxyadenocobalamin, folic acid, tetrahydrofolic acid, dihydrofolic acid, nicotinic acid, nicotinamide, nicotinyl alcohol, pantothenic acid, bread threonine, biotin, choline, inositol, etc.], vitamin C [for example, ascorbic acid, salts of ascorbic acid, erythorbic acid, or derivatives thereof, etc.], vitamin D [for example, ergocalciferol, cholecalciferol, hydroxycholecalciferol, dihydroxycholecalciferol, dihydrotachysterol, etc.], vitamin E [for example, tocopherol and its derivatives, ubiquinone derivatives, etc.], other vitamins [for example, hesperidin, carnitine, ferulic acid, γ-oryzanol, orotic acid, rutin, eriocitrin, etc.], collagen (including hydrolyzed collagen), hyaluronic acid (including hydrolyzed hyaluronic acid), lactoferrin, polyphenols, etc. Among these, water-soluble vitamins are preferred, and ascorbic acid and / or its salts, or water-soluble vitamins including vitamin B are more preferred, and ascorbic acid and / or its salts are even more preferred.
[0031] The desired component being "encompassed" in the liposome may mean any of the following: being enclosed in the space within the liposome membrane, being present together with a component of the liposome membrane, being present between the multiple membranes that make up the liposome, or being bound to or attached to the surface of the outermost membrane that makes up the liposome.
[0032] The size of the liposome is usually about 30 to 1000 nm, preferably 30 to 600 nm, and more preferably 50 to 200 nm.
[0033] With respect to the liposomes in this specification, the components encapsulated in the liposomes may be expressed as "liposomal components of interest". For example, liposomes encapsulating vitamins may be expressed as "liposomal vitamins", "vitamin-encapsulating liposomes", "vitamin-containing liposomes", "liposomal vitamins", etc. Liposomes encapsulating ascorbic acid may be expressed as "liposomal ascorbic acid", "liposomes encapsulating ascorbic acid", "liposomes containing ascorbic acid", "liposomes containing ascorbic acid", "liposomes encapsulating ascorbic acid", "liposomes containing ascorbic acid", "liposomal ascorbic acid", etc.
[0034] Liposomes containing the desired components can be produced by a conventional method. For example, lecithin and optionally sterols are solubilized in a solvent such as ethanol, the solvent is removed under reduced pressure to prepare membrane lipids, and then a solution containing the desired components is added thereto and stirred to prepare a liposome suspension, thereby obtaining liposomes containing the components.
[0035] In addition to these methods, liposomes can also be obtained by dissolving lecithin and, optionally, a sterol in a small amount of ethanol, dispersing the mixture in an aqueous solution or buffer solution to perform pre-emulsification, and dispersing the mixture under high pressure to form a lipid bilayer to prepare a liposome suspension.
[0036] The liposome is preferably a liposome containing a water-soluble component, more preferably a liposome containing a water-soluble vitamin, and even more preferably a liposome containing ascorbic acid and / or a salt thereof. Such liposomes can be obtained by preparing the water-soluble component as the desired component by the above-mentioned method. Alternatively, a commercially available product can be used as the liposome. For example, a commercially available product of liposome containing ascorbic acid is "Vitamin C Zeal" (Aurea Bio).
[0037] In the granules of the present invention, the total content of liposomes relative to the total amount is 0.1% by mass or more, more preferably 1% by mass or more, even more preferably 3% by mass or more, and even more preferably 5% by mass or more. The total content of liposomes relative to the total amount of the granules is preferably 80% by mass or less, more preferably 70% by mass or less, even more preferably 50% by mass or less, and most preferably 20% by mass or less.
[0038] The content of the desired component in the liposome containing the desired component is preferably about 10 to 99% by mass, more preferably about 20 to 95% by mass, even more preferably about 25 to 90% by mass, and even more preferably 30 to 70% by mass.
[0039] For example, the content of ascorbic acid in liposomes containing ascorbic acid and / or a salt thereof is preferably about 10 to 99% by mass, more preferably about 20 to 95% by mass, even more preferably about 25 to 90% by mass, and even more preferably 30 to 70% by mass.
[0040] (Vitamins) The granules of the present invention may contain pharmacologically active or physiologically active ingredients other than the component (B) within a range that does not impair the effects of the present invention. The pharmacologically active or physiologically active ingredients may be used alone or in combination of two or more. Such ingredients include, but are not limited to, various vitamins, peptides, etc.
[0041] Examples of vitamins include vitamin A [e.g., retinal, retinol, retinoic acid, carotene, dehydroretinal, lycopene, etc.], vitamin B [e.g., thiamine, thiamine disulfide, dicethiamine, octotiamine, shikotiamine, bis-ibuthiamine, bis-bentiamine, prosultiamine, benfotiamine, fursultiamine, riboflavin, flavin adenine dinucleotide, pyridoxine, pyridoxal, hydroxocobalamin, cyanocobalamin, methylcobalamin, deoxyadenocobalamin, folic acid, tetrahydrofolic acid, dihydrofolic acid, nicotinic acid, nicotinamide, nicotinic acid ... vitamin C [e.g., ascorbic acid, salts of ascorbic acid, erythorbic acid, and derivatives thereof], vitamin D [e.g., ergocalciferol, cholecalciferol, hydroxycholecalciferol, dihydroxycholecalciferol, dihydrotachysterol], vitamin E [e.g., tocopherol and its derivatives, ubiquinone derivatives], and other vitamins [e.g., hesperidin, carnitine, ferulic acid, γ-oryzanol, orotic acid, rutin, eriocitrin].
[0042] In one embodiment of the present invention, among these, vitamin B and vitamin C are preferred, and as vitamin C, ascorbic acid or a salt thereof, or a water-soluble ascorbic acid derivative is preferably used, more preferably ascorbic acid or a salt thereof. Ascorbic acid is more preferably usually in the L-form.
[0043] Examples of salts of ascorbic acid include alkali metal salts, alkaline earth metal salts, and ammonium salts. Examples of alkali metal salts include sodium salts, potassium salts, and lithium salts. Examples of alkaline earth metal salts include calcium salts and magnesium salts.
[0044] Preferred salts of ascorbic acid are the sodium salt or magnesium salt.
[0045] Preferred water-soluble ascorbic acid derivatives include ascorbic acid oxidase, calcium L-ascorbate, L-ascorbic acid 2-glucoside, L-ascorbic acid stearate, sodium L-ascorbate, L-ascorbic acid palmitate, erythorbic acid, sodium erythorbate, and the like.
[0046] The content of such vitamin C is, for example, preferably 1% by mass or more, more preferably 5% by mass or more, even more preferably 10% by mass or more, and even more preferably 30% by mass or more, based on the total amount of the granule. The total content of vitamin C is preferably 95% by mass or less, more preferably 90% by mass or less, even more preferably 85% by mass or less, and most preferably 80% by mass or less, based on the total amount of the granule. It may also be 40% by mass or more, 50% by mass or more, 60% by mass or less, 70% by mass or less, 60% by mass or less, 50% by mass or less, 40% by mass or less, etc.
[0047] Among these, the vitamin B group is preferably a water-soluble vitamin, and particularly preferably vitamin B2. The content of such vitamin B group is, for example, preferably 0.5% by mass or more, more preferably 1% by mass or more, and even more preferably 1.2% by mass or more, based on the total amount of the granule. The content of vitamin B2 group is preferably 3% by mass or less, more preferably 2% by mass or less, and even more preferably 1.5% by mass or less.
[0048] (Additives) The granules of the present invention may contain additives within the range that does not impair the effects of the present invention. Specific examples of such additives include binders, flow improvers / anti-caking agents, sugar alcohols, oils and fats, flavors, excipients, disintegrants, lubricants, colorants, flavorings, odorants, sugars, polyhydric alcohols, high-intensity sweeteners, emulsifiers, thickeners, acidulants, fruit juices, etc.
[0049] Examples of the binder include cellulose derivatives such as methyl cellulose, ethyl cellulose, hydroxypropyl cellulose, and hydroxypropyl methyl cellulose, polyvinyl pyrrolidone, polyvinyl alcohol, acrylic acid polymers, gelatin, gum arabic, pullulan, pregelatinized starch, agar, tragacanth, sodium alginate, and propylene glycol alginate. Among these, cellulose derivatives are preferred.
[0050] The content of the binder is, for example, preferably 1% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more, based on the total amount of the granules, and is preferably 20% by mass or less, more preferably 15% by mass or less, and even more preferably 10% by mass or less.
[0051] As the flow improver and anti-caking agent, silicon dioxide is preferred, and fine silicon dioxide is more preferred.
[0052] The content of such fine silicon dioxide is, for example, preferably 0.5% by mass or more, more preferably 0.8% by mass or more, and even more preferably 1% by mass or more, based on the total amount of the granule. The content of fine silicon dioxide is preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 2% by mass or less.
[0053] Examples of sugar alcohols include lactose, maltose, fructose, sorbitol, maltitol, mannitol, xylitol, and trehalose.
[0054] The coloring agent may be a natural colorant, and for example, marigold color or the like is preferably used.
[0055] Of these, the additives are preferably, but not limited to, a combination of a binder, a flow improver / anti-caking agent and / or a colorant.
[0056] (Properties of granules) The granules of the present invention may have an average particle size of preferably 250 μm or more, more preferably 350 μm or more, and even more preferably 500 μm or more. The average particle size of the granules may be preferably 2000 μm or less, more preferably 1500 μm or less, and even more preferably 1200 μm or less. The average particle size is measured using a laser diffraction particle size measuring device (Malvern Panalytical Ltd. Mastersizer 3000) or according to the sieving method of the 18th Edition of the Japanese Pharmacopoeia.
[0057] The granule of the present invention may have an aspect ratio of 1 or more, preferably 3.5 or less, more preferably 3 or less, even more preferably 2.5 or less, and even more preferably 2 or less. The aspect ratio is the ratio of the minor axis to the major axis of a particle (major axis of a particle / minor axis of a particle), and is an index of sphericity. The major axis and minor axis are measured, for example, with a digital microscope (Keyence VHX-8000), and the average value of 10 measurements can be used.
[0058] Regarding the particle size of the granules of the present invention, when the ratio of granules having a size of 710 μm to 1410 μm is defined as M1 and the ratio of granules having a size of 250 to 500 μm is defined as M2, the particle size distribution ratio (M1 / M2) is preferably 40 or less, more preferably 30 or less, and further preferably 25 or less. (A / B) is preferably 2.5 or more, more preferably 2.7 or more, and even more preferably 3 or more. It may be 5 or more, 7 or more, 10 or more, 15 or more, 20 or more, etc. The particle size distribution ratio is determined by the ratio (M1 / M2) of the proportion of granules of 710 μm to 1410 μm to the proportion of granules of 250 to 500 μm in particle size measurement of powder particles. The particle size of powder particles is measured using a laser diffraction particle size measuring device (Mastersizer 3000 manufactured by Malvern Panalytical Ltd) or according to the sieving method of the 18th revised edition of the Japanese Pharmacopoeia.
[0059] Regarding the particle size of the granules of the present invention, the particle size distribution ratio (M3 / M4) where the ratio of granules of 500 μm to 1410 μm is M3 and the ratio of granules of 250 to 355 μm is M4, may be preferably 60 or less, more preferably 50 or less, and further preferably 40 or less. The particle size distribution width (M3 / M4) may be preferably 7 or more, more preferably 10 or more. It may be 15 or more, 20 or more, 30 or more, etc. The particle size distribution ratio is determined by the ratio (M3 / M4) of the mass of granules of 500 μm to 1410 μm to the mass of granules of 250 to 355 μm in particle size measurement of powder particles.
[0060] The particle size of the granules of the present invention is preferably such that the amount of granules having a particle size of 255 to 355 μm is small. The amount is preferably 10% by mass or less, more preferably 8% by mass or less. It may be 6% by mass or less, 5% by mass or less, etc.
[0061] The particle size of the granules of the present invention is preferably such that the amount of granules of 250 μm or less is small, preferably 10% by mass or less, more preferably 5% by mass or less, even more preferably 3% by mass or less, and even more preferably 2% by mass or less.
[0062] The surface roughness (Ra) of the granule of the present invention may be preferably 40 or less, more preferably 35 or less, even more preferably 30 or less, and even more preferably 25 or less. Ra is preferably 1 or more, more preferably 3 or more, and even more preferably 7 or more. The surface roughness can be measured using a digital microscope (Keyence VHX-8000).
[0063] [Manufacturing method] The method for producing the granules of the present invention is not particularly limited, and known methods can be used. Specifically, the method includes the steps of mixing (A) crystalline cellulose and (B) mucopolysaccharide to prepare a mixture, and kneading and granulating the mixture. Here, a commonly used granulation method can be used for granulation. For example, wet granulation methods such as spray granulation, stirring granulation, extrusion granulation, fluidized bed granulation, rolling granulation, and rolling fluidized bed granulation, and dry granulation methods such as compaction granulation can be used. Among these, although not limited thereto, it is preferable to use a wet granulation method, especially an extrusion granulation method or a rolling granulation method, from the viewpoint of the mechanism assumed by the inventor and enhancing the effect of the invention.
[0064] In the present invention, even when granules are produced through a normal granulation process, fine powder can be suppressed, and the obtained granules have a good appearance close to a perfect circle. The contents of each component and other conditions in the production method are in accordance with the contents described in [Granules].
[0065] [Methods for preventing fine powder generation during manufacturing] One aspect of the present invention relates to a method for suppressing the generation of fine powder in the manufacturing process of granules, that is, a method for suppressing the generation of fine powder by granulating (A) crystalline cellulose in the presence of (B) mucopolysaccharide. Here, fine powder refers to, for example, powder of 250 μm or less. Preferably, the amount of 250 μm powder immediately after the production of granules is suppressed to 20 mass % or less. Preferably, it means that the amount is suppressed to 10 mass % or less, more preferably 5 mass % or less, even more preferably 3 mass % or less, and particularly preferably about 2 mass % or less. The content of each component and other conditions in this method are the same as those described in [Granules].
[0066] [Formulation] The granules of the present invention can be used as they are or can be used after being packaged in a package. The granules of the present invention can also be molded into tablets, but in order to ensure the aesthetic appearance of the present invention, it is preferable to use them as granules. Here, the package can be SP packaging, stick packaging, or a hard capsule. Among these, it is preferable to use them as a hard capsule from the viewpoint of ease of handling and aesthetics, and it is more preferable to use a soft capsule or hard capsule packaged in a transparent or semitransparent container that allows the contents to be visually confirmed. The entire capsule may be transparent or semitransparent, or a part of the capsule (e.g., half) may be transparent or semitransparent. Here, transparency or semitransparency refers to the shape of the contents of the capsule that can be confirmed at an optimal distance by an adult with a visual acuity of 0.5 or more when visually observing the capsule from the outside.
[0067] The capsule may be a hard capsule container containing a layer containing hydroxypropylmethylcellulose. That is, the granule of the present invention may be contained in a capsule container having a layer containing hydroxypropylmethylcellulose on the surface in contact with the granule. The layer containing hydroxypropylmethylcellulose may be a layer consisting of hydroxypropylmethylcellulose only, but the ratio is not limited as long as it contains hydroxypropylmethylcellulose. The capsule may be a capsule containing one or more components selected from the group consisting of agar, carrageenan, and gelatin. Here, the capsule may be multi-layered or single-layered.
[0068] The minor axis / major axis ratio when the capsule body and cap are combined is not particularly limited, but is preferably about 0.30 to 0.42, and more preferably about 0.35 to 0.40.
[0069] [Use and dosage, etc.] The granules of the present invention can be used as ingredients of, for example, medicines, quasi-drugs, cosmetics, and food and drink (drinks, foods). The granules according to the present embodiment can also be used as foods such as, for example, foods for specified health uses, foods with nutritional functions, foods for the elderly, foods for special dietary uses, foods with functional claims, dietary supplements, and food preparations (e.g., confectionery tablets) in addition to pharmaceutical preparations and quasi-drug preparations. EXAMPLES
[0070] The present invention will now be described in detail with reference to examples and test examples, but the present invention is not limited to the following examples and test examples. The unit of each component amount in the tables is mass % unless otherwise specified. The following reagents were used: Liposome VC: Ascorbic acid-containing liposome (Product name: Vitamin C Zeal: Alpha Link Co., Ltd., Test example 3: Product name: Liposomal PureWay-C Fine Powder: Maypro Industries Co., Ltd.) Hyaluronic acid (Product name: Low molecular weight hyaluronic acid: Chori Co., Ltd.) Silicon dioxide (Product name: Silopage 720: Fuji Silysia Chemical Ltd.) Crystalline cellulose (product name: Ceolas-ST100: Asahi Kasei Corporation)
[0071] [Test Example 1. Water Absorption Verification Test] Compositions of the examples and comparative examples having the formulations shown in Table 1 below were prepared. Each component shown in the table was weighed, placed in a plastic bag, and mixed by hand. 50 g was removed from the plastic bag and placed in an automatic mortar machine, and 10 g of water was added. After kneading for 1 minute in the automatic mortar machine, any adhering material on the side of the mortar was scraped off, and the mixture was returned to the mortar and kneaded for another minute to obtain each composition.
[0072] Each kneaded composition was laid flat on a flat plate, and tissue (product name: Nepia Tissue 200W, Oji Nepia Co., Ltd.) was placed on top. A 500 mL glass beaker containing 400 mL of water was then placed on top at room temperature of 25°C ± 3°C and humidity of 55 ± 10% RH for 10 minutes, and the tissue was collected and immediately weighed.
[0073] The amount of water absorbed into the tissue (MB-MA) and each water absorption increase rate were calculated from the mass of the original tissue (MA) and the mass of the tissue after water absorption (MB). Next, the water absorption improvement rate of the compositions of the Examples was calculated based on the water absorption increase rate of each composition and the water absorption increase rate of the composition of the Reference Example. Furthermore, the water absorption improvement rate of the compositions of the Comparative Examples was also calculated based on the Reference Comparative Example, and the improvement rates were compared. The more the water absorption into the tissue is suppressed, the higher the water absorption rate of the composition. Water absorption increase rate = [((MB-MA) / MA) x 100] Water absorption improvement rate % = [100 × (water absorption increase rate of each corresponding reference example / water absorption increase rate of each corresponding comparative example or example)] Here, the corresponding reference examples and the corresponding comparative examples or examples respectively have the following meanings. That is, Reference Example 1 and Example 1-1; Reference Example 2 and Comparative Example 1-1.
[0074] Furthermore, the bulk density of each composition was measured according to the bulk density and tap density measurement method in the general testing methods of the 18th revised Japanese Pharmacopoeia. Bulk density improvement rate %=100×(bulk density of each corresponding comparative example or example / bulk density of each corresponding reference example) The obtained water absorption improvement rate and bulk density are shown in Table 1. [Table 1] From the results shown in Table 1, it was found that the compositions of the examples had significantly improved water absorption and higher bulk density than the compositions of the comparative examples. Therefore, it was expected that heavy granules with less fine powder would be produced when granulated.
[0075] [Test Example 2. Micronization Confirmation Test] Compositions of the examples and comparative examples having the formulations shown in Table 2 below were prepared. Each component shown in the table was weighed, all components were premixed, further mixed, and kneaded in a stirring mixer while adding water to the powder, and then granulated and molded by extruding in an extrusion granulator. The obtained granules were measured for particle size: tare weight of each sieve (1410, 1180, 710, 500, 355, 250 μm mesh size) according to the sieving method of the Japanese Pharmacopoeia, 18th Edition. The sieves were stacked in order of size of mesh size so that the 1410 μm mesh size was on the top sieve, and about 10 g of granules was placed on the top sieve, covered, and the sieve set was shaken for 3 minutes. The mass of each sieve was then measured again, and the mass of the granules on the sieves was calculated.
[0076] Furthermore, the mass of the powder that passed through the 250 μm sieve was measured, and the ratio to the mass of all components was calculated. The results are shown in the table. In the table, values other than "250 pass" are the measured values of granules that did not pass through the 250 sieve.
[0077] [Table 2]
[0078] From the results shown in Table 2, it was confirmed that the compositions of the Examples suppressed pulverization after granulation molding and reduced production loss compared to the compositions of the Comparative Examples. In the compositions of the Examples, the components over 710 μm sieve and under 1410 μm sieve were more than 80%, whereas in the compositions of the Comparative Examples, the components were less than 70%. In addition, it was visually confirmed that the granules obtained in the examples were nearly perfectly round, had a smooth surface, a beautiful appearance, and were uniform in size. It was also confirmed that the surface roughness was actually kept low. On the other hand, the granules obtained from the composition of the comparative example had jagged areas on the surface and the particles were not uniform, even though they were produced under the same granulation conditions.
[0079] [Test Example 3. Appearance Evaluation Test] Each composition of the examples and comparative examples having the composition shown in Table 2 was prepared and enclosed in a transparent capsule (product name: QUALI-V-N (No. 1 transparent), Qualicaps Co., Ltd.). Ten subjects who are familiar with the evaluation of capsule formulations evaluated the visual analog scale (VAS) value of the aesthetic appearance of the obtained capsule formulation. The average value (average VAS value) was used as the aesthetic value (beauty value). The maximum scale of the VAS scale was 10. The results are shown in Table 3.
[0080] <Evaluation criteria> 10 points: The granules had a glossy surface, the colors were vivid, and it felt like a high-quality product.
[0081] [Table 3]
[0082] As a result, it was confirmed that the capsule formulations containing the granules obtained from the composition of the embodiment had excellent aesthetic appearance, while the granules obtained from the composition of the comparative example were clearly inferior in aesthetic appearance. Furthermore, for each of the capsule formulations, the evaluation results of all subjects were within the range of ±1.
[0083] Granules were prepared according to the table below and filled into transparent capsules. (The excipients and capsules were the same as those used in the examples.) In all formulations, the effects of the present invention were achieved, such as suppressing pulverization after granulation and minimizing production loss, and excellent appearance. [Table 4]
Claims
1. A granule containing (A) crystalline cellulose and (B) mucopolysaccharide.
2. 2. The granule according to claim 1, having an average particle size of 250 μm or more.
3. The granule according to claim 1, wherein the total content of the component (B) is 0.00001 to 40 parts by mass per part by mass of the component (A).
4. The granule according to claim 1, having an aspect ratio of 1.0 to 3.
5.
5. 2. The granule according to claim 1, wherein the particle size distribution ratio (M1 / M2) is 2.5 or more and 40 or less.
6. 2. The granule according to claim 1, having a surface roughness (Ra) of 1 or more and 40 or less.
7. The granule according to claim 1, which is enclosed in a package in which the contents can be visually confirmed.
8. The granule according to claim 1, wherein the component (B) is hyaluronic acid.
9. A step of mixing (A) crystalline cellulose and (B) mucopolysaccharide to prepare a mixture; and and kneading and granulating the mixture.
10. A method for suppressing the generation of fine powder during granulation of a mixture containing (A) crystalline cellulose and (B) a mucopolysaccharide.
Citation Information
Patent Citations
Composite granule comprising sugar or sugar alcohol, swellable binder, disintegrator and superabsorbent excipient and method for producing the same
JP2017071561A